Chicken Cage Incubator Cooling Control System Using Fuzzy Logic - Agni Dhewa, Oktaf; Aldiasa Pangestu Aji (Media of Computer Science, 2024)
This research examines the impact of prolonged cooling time in the incubator of chicken coops on the well-being of chicks during the incubation process. Poorly maintained temperature conditions can jeopardize the health of chicks and diminish the overall productivity of poultry farming. To address this issue, the study develops an efficient temperature control system by integrating a peltier as the main cooling component and fuzzy logic control combined with a DC fan. Experimental results indicate that the developed system is capable of providing a robust response to temperature changes in the chicken coop incubator, with transient response values meeting the expected criteria. Consequently, this temperature control system holds the potential to enhance the performance of chicken coop incubators and reduce the risk of chick mortality during the incubation process. This research serves as an initial step in advancing better temperature control for chicken coop incubators in the future.